Diachronic Monitoring of Psatha Active Fault at a Costal Zone, by Combining Near Surface Geophysical Methods - Katsora, C; Vassilakis, E; Konsolaki, A.; Alexopoulos, J.D. (NSG2023, 29th European Meeting of Environmental and Engineering Geophysics, 2023)
Light Detection And Range (LiDAR) data have been used in numerous case studies, related to fast-developing landslides and rockfalls, producing remarkably precise Digital Terrain Models (DTMs). When these models are coupled to classic near-surface geophysical methods, they result in the high-accuracy mapping of the open surface and subsurface morphology, an essential element for a modern coastal management study. In this work, we introduce the diachronic monitoring and detection of alterations on the surface of the active fault of Psatha (Greece), via a multiple-phase study within a period of 11 years, by using terrestrial LiDAR scans and Electrical Resistivity Tomography (ERT). The successful combination of these techniques is being used to reveal and quantify the landscape evolution involving the surface alterations at the fault adjacent coastal zone, the sea intrusion, and even the coastline displacement, in any coastal area characterized by similar features.